Evaluating the effect of daytime sleepiness and sleep quality on balance, fatigue and life quality of shift workers - Do?an, Semanur; Aras Bayram, Gülay (IOS Press BV, 2024)
BACKGROUND: Changes in the sleep-wake cycle in shift workers can cause many health problems. OBJECTIVE: The aim of this study was to investigate the relationship between daytime sleepiness and sleep quality on balance, physical activity level, fatigue and quality of life in shift and non-shift workers. METHOD: A total of 58 employees, 29 shifts and 29 non-shifts, were included in the study. Data were collected using the Epworth Sleepiness Scale, the Pittsburgh Sleep Quality Index, the Tandem Posture Test, the One-Foot Stand Test, the Ten-Step Tandem Walking Test, the International Physical Activity Questionnaire-Short Form, the Fatigue Severity Scale, and the Nottingham Health Profile. RESULTS: Individuals working in shifts had higher fatigue severity and daytime sleepiness levels (p < 0.05), while physical activity levels and sleep quality were lower than those working without shifts (p < 0.05). It was determined that as the daytime sleepiness of individuals working in shifts and non-shifts increased, their quality of life decreased (p < 0.05). CONCLUSION: According to the data obtained from the study, individuals working in shifts compared to individuals working without shifts experienced higher levels of daytime sleepiness and fatigue severity level while sleep quality and physical activity level were lower.
Keywords: Balance; Daytime Sleepiness; Quality of Life; Shift Work; Sleep Quality; Worker